2018
DOI: 10.3390/met8120988
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Difference in Bainite Transformation with Varying the Prior Austenite Grain Size in Low Carbon Steel

Abstract: The simulation welding thermal cycle technique was employed to generate different sizes of prior austenite grains. Dilatometry tests, in situ laser scanning confocal microscopy, and transmission electron microscopy were used to investigate the role of prior austenite grain size on bainite transformation in low carbon steel. The bainite start transformation (Bs) temperature was reduced by fine austenite grains (lowered by about 30 °C under the experimental conditions). Through careful microstructural observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Papaefthymiou et al [9] have shown that the UFH of medium carbon CrMo steels results in a multiphase fine microstructure consisting of martensite, bainite, undissolved cementite and retained austenite with grain average diameter less than 2 µm. The reason is that the ferrite to austenite phase transformation during ultra-fast heating creates chemically and structurally (morphologically) heterogeneous austenite with very fine grains, which transform after quenching to mixtures of bainite and martensite, while finely dispersed carbides remain partly dissolved or in their initial condition [10]. The presence of bainite in the microstructure was studied also by Banis et al [11] and Cerda et al [12].…”
Section: Introductionmentioning
confidence: 97%
“…Papaefthymiou et al [9] have shown that the UFH of medium carbon CrMo steels results in a multiphase fine microstructure consisting of martensite, bainite, undissolved cementite and retained austenite with grain average diameter less than 2 µm. The reason is that the ferrite to austenite phase transformation during ultra-fast heating creates chemically and structurally (morphologically) heterogeneous austenite with very fine grains, which transform after quenching to mixtures of bainite and martensite, while finely dispersed carbides remain partly dissolved or in their initial condition [10]. The presence of bainite in the microstructure was studied also by Banis et al [11] and Cerda et al [12].…”
Section: Introductionmentioning
confidence: 97%
“…The present Special Issue on Thermomechanical Processing of Steels includes eleven research papers [1][2][3][4][5][6][7][8][9][10][11]. A wide range of steel grades are covered in these papers.…”
Section: Contributionsmentioning
confidence: 99%
“…A wide range of steel grades are covered in these papers. Although most of the papers deal with low carbon microalloyed grades [1,3,6,9,10], several papers study ferritic stainless steels [2,5,7] and others focus on grades such as Fe-Al-Cr alloys [4], medium-Mn Nb microalloyed steels [8], and medium carbon V microalloyed grades [11].…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations